Retroperitoneal dedifferentiated liposarcoma with colon infiltration: a case report and literature review - Tu, Xi; Zhuang, Xiyao; Huang, Chaoyou (Frontiers in Oncology, 2025)
Retroperitoneal dedifferentiated liposarcoma (RP DDLS) is considered highly malignant, with a high recurrence rate and poor prognosis, and is usually asymptomatic until the advanced stages. Retroperitoneal liposarcoma with colon invasion is extremely rare, with only a few cases reported in the literature. This study reported the case of a 75-year-old male patient with a retroperitoneal space-occupying lesion without any clinical symptoms. Abdominal computed tomography (CT) and magnetic resonance imaging (MRI) scans suggested a neoplastic lesion. After adequate preoperative preparation, the patient underwent laparoscopic tumor resection and right hemicolectomy. Pathological and immunohistochemical examinations of the resected retroperitoneal mass and right hemicolon revealed dedifferentiated liposarcoma (DDLPS). Dedifferentiated liposarcomas are characterized by local invasiveness and a high recurrence rate. The association between dedifferentiated liposarcoma and invasive behavior observed in this patient underscores the importance of multidisciplinary collaboration as the primary treatment strategy. Nevertheless, complete tumor resection remains crucial for improving the prognosis and reducing the high local recurrence rate.